2012
DOI: 10.1021/op300034u
|View full text |Cite
|
Sign up to set email alerts
|

Corey–Itsuno Reduction of Ketones: A Development of Safe and Inexpensive Process for Synthesis of Some API Intermediates

Abstract: A safe and inexpensive procedure for asymmetric reduction of ketones using in situ prepared N,N-diethylaniline borane (DEANB) and oxazaborolidine catalyst from sodium borohydride, N,N-diethylaniline hydrochloride and (S)-α,α-diphenylprolinol is described. This protocol is demonstrated successfully to manufacture enantiopure dapoxetine at the plant scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…While this process was successfully employed for the first-generation campaign, we recognized that this could pose challenges during future campaigns primarily due to the moderate diastereoselectivity observed in the reaction as well as the capacity and availability of the hydrogenator for larger scales. Mahale et al reported a highly diastereoselective protocol for the asymmetric reduction (Corey–Itsuno reduction) of prochiral ketones using a CBS (Corey–Bakshi–Shibata) catalyst and diethylphenylamine-borane (BH 3 ·PhNEt 2 ), and we sought to extrapolate these conditions for the diastereoselective reduction of 13 . We were pleased to observe that the use of 10 mol % ( R )-2-methyl-CBS-oxazaborolidine and 1.0 equiv of BH 3 ·PhNEt 2 in toluene led to clean reduction of 13 to provide a 67:1 ratio of diastereomers 8 and 15 in nearly quantitative conversion (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…While this process was successfully employed for the first-generation campaign, we recognized that this could pose challenges during future campaigns primarily due to the moderate diastereoselectivity observed in the reaction as well as the capacity and availability of the hydrogenator for larger scales. Mahale et al reported a highly diastereoselective protocol for the asymmetric reduction (Corey–Itsuno reduction) of prochiral ketones using a CBS (Corey–Bakshi–Shibata) catalyst and diethylphenylamine-borane (BH 3 ·PhNEt 2 ), and we sought to extrapolate these conditions for the diastereoselective reduction of 13 . We were pleased to observe that the use of 10 mol % ( R )-2-methyl-CBS-oxazaborolidine and 1.0 equiv of BH 3 ·PhNEt 2 in toluene led to clean reduction of 13 to provide a 67:1 ratio of diastereomers 8 and 15 in nearly quantitative conversion (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…5 It was expected to be prepared by the condensation of 3-chloro-propiophenone with 1-naphthol under NaOH aq THF solution (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Codexis used an ADH variant from Lactobacillus kefir with 2-propanol for NADPH-recycling to perform this stereoselective reduction. A substrate loading of 100 g·L –1 and a catalyst loading of 1.0 g·L –1 gave 48.0 g (96%) of ( S )-licarbazepine with >99.9% e.e. , The asymmetric chemical reduction has also been reported with a chiral CBS catalyst. , The method allowed the conversion of 350 g (49 g·L –1 ) of oxcarbazepine, yielding 321.7 g (91%) of ( S )-licarbazepine with 98.5% chemical purity and 99% e.e. In comparison, the biocatalytic reduction resulted in a little higher yield; the chemical reduction required cooling (−5 to 10 °C) and was performed in organic solvents (dichloromethane and toluene) …”
Section: Functional Groups Formed In Biocatalytic Reactions For Api S...mentioning
confidence: 89%
“…126,128 The asymmetric chemical reduction has also been reported with a chiral CBS catalyst. 127,129 The method allowed the conversion of 350 g (49 g•L −1 ) of oxcarbazepine, yielding 321.7 g (91%) of (S)licarbazepine with 98.5% chemical purity and 99% e.e. In comparison, the biocatalytic reduction resulted in a little higher yield; the chemical reduction required cooling (−5 to 10 °C) and was performed in organic solvents (dichloromethane and toluene).…”
Section: Alcoholsmentioning
confidence: 99%